Impact of the Covid-19 pandemic on the management of gynecologic cancer: a Spanish survey. Observational, multicenter study - Myriam Gracia; Elena Rodríguez; María Dolores Diestro; Emanuela Spagnolo; Virginia García; Jaime Siegrist; Yolanda Pérez; Ignacio Zapardiel; Alicia Hernández (BMC, 2023)
Abstract Background The SARS-CoV-2 (Severe Acute Respiratory Syndrome Coronavirus 2) pandemic changed the distribution of healthcare resources, leading in many cases to the suspension of all non-essential treatments and procedures and representing a challenge for medical professionals. The objective of this study was to evaluate whether clinical protocols in gynecologic oncology care were modified as a result of the pandemic and to assess surgeons' perceptions regarding the management of gynecologic cancers". Methods Data were collected through an anonymous and voluntary survey sent via email to healthcare professionals in the field of gynecologic oncology in Spain. Results A total of 75 gynecologic oncologists completed the online survey. Of these, 93.2% (69) reported working in public hospitals and 62.5% (45) in tertiary care hospitals. 97.3% (71) were affiliated with hospitals treating patients infected with SARS-CoV-2. 85.1% (63) of the respondents expressed concern about the SARS-CoV-2 pandemic and 52.1% (38) indicated that the pandemic impacted the diagnostic and therapeutic quality of care for oncology patients. SARS-CoV-2 nasopharyngeal swab PCR (Polymerase Chain Reaction) testing was always performed before surgical interventions by 97.3% (71), being considered a best practice in triage by 94.4% (68). 87.5% (63) reported no change in the type of surgical approach during the pandemic. 62.5% (45) experienced limitations in accessing special personal protective equipment for SARS-CoV-2. An impact on the follow-up of patients with gynecologic cancers due to the pandemic was reported by 70.4% (50). Conclusions Most of the Spanish gynecologic oncologists who responded to our survey reported that the SARS-CoV-2 pandemic had affected their clinical practice. The primary measures implemented were an increase in telemedicine, restricting outpatient visits to high-risk or symptomatic patients and the use of SARS-CoV-2 screening prior to surgery. No major changes in the surgical approach or management of the treatment of ovarian, endometrial or cervical cancer during the pandemic were reported.